Aktualisasi Humanisme Religius Menuju Humanisme Spiritual dalam Bingkai Filsafat Agama - Husna Amin (Fakultas Ushuluddin dan Filsafat UIN Ar-raniry Banda Aceh, 2013)
An understanding of the universal values of human existence that does not differ individually, an attitude humanistic into the spirit of the movement of religious and philosophical. Humanism was born in the spectrum of modern thought, just fight for these values. But in its development, teaching the humanities have negative implications in addition to providing positive things for the spirit of humanity. Behind these two spheres, it must be admitted that neither philosophy nor religion, basically moving and growing in a single purpose, which is to fight for and defend human life order. Both will not be meaningful, if it does not consider the value of humanity. Religious Humanism is a philosophical connectivity that determines the course of human life taken is objective, rational, ethical and religious. Human freedom is a central theme religious humanism, but the freedom he fought for freedom not absolute or medieval antithesis which incidentally is considered balanced between religious interests and the interests of humanity. Man is the center of reality, so everything must be returned to him and the phenomenon of human existence is not justified interpretation of the phenomenon that place people as marginal entities